Building up rehabilitation services as we wait to hold patients' hands again. (2nd April 2021) - Drake, Nicola
Abstract : Nicola Drake reflects on her team's achievements in using technology to build up their cardiac rehabilitation services to provide safe and effective care, while staff await the day they can once again hold patients' hands.